IMPLEMENTASI KEBIJAKAN PEMBERDAYAAN MASYARAKAT PESISIR DI KELURAHAN TANJUNG MAS KOTA SEMARANG - Lea Prastika; Kismartini Kismartini (Journal of Public Policy and Management Review, 2017)
Empowerment of coastal communities as one solution to increase the welfare of society at this time has not been well established. About 32.4% of coastal communities in Indonesia are still in the poverty line as a result of the management of coastal areas are less precise. This study aims to analyze the implementation of coastal communities empowerment policy in the Villages of Tanjung Mas as well as identify the factor are supporting and inhibiting implementation than to formulate efforts that we need to create for the effectively implementation of coastal communities empowerment policy. The results showed that the implementation of Perda Semarang No. 23 in 2011 about the management of coastal area has not yet reached the goal of empowerment according. This occurs because the existence of NGOS as implementing community empowerment actors not yet seen, community empowerment for individuals not yet implemented, the Government of Semarang City have not compiled technical guidelines at the discretion of coastal communities empowerment, and the distribution of beneficiaries of policies have not been evenly distributed. Based on the shortage of necessary efforts increased participation of NGOS, draw up technical guidelines for coastal community empowerment as a priority, doing mapping of potential inhabitants, and encouraging the public to participate in environmental conservation.